Alteration of Skin Microbiome in CKD Patients Is Associated With Pruritus and Renal Function - Tian, Yu; Gu, Chaoqun; Yan, Feng; Gu, Yifeng; Feng, Yangkun; Chen, Jie; Sheng, Jiayi; Hu, Lei; Jiang, Peng; Guo, Wei; Feng, Ninghan (Frontiers in Cellular and Infection Microbiology, 2022)
Dysbiotic gut microbiome in chronic kidney disease (CKD) patients has been extensively explored in recent years. Skin microbiome plays a crucial role in patients with skin diseases or even systemic disorders. Pruritus is caused by the retention of uremic solutes in the skin. Until now, no studies have investigated the role of skin microbiome in CKD and its association with pruritus. Here, we aim to examine the bacterial profile of skin microbiome in CKD and whether it is correlated to pruritus. A total of 105 CKD patients and 38 healthy controls (HC) were recruited. Skin swab was used to collect skin samples at the antecubital fossa of participants. Bacterial 16S rRNA genes V3–V4 region was sequenced on NovaSeq platform. On the day of skin sample collection, renal function was assessed, and numeric rating scale was used to measure pruritus severity. Principal coordinate analysis (PCoA) revealed a significant difference in bacterial composition between the groups of CKD and HC. A depletion of bacterial diversity was observed in CKD patients. Akkermansia, Albimonas, Escherichia–Shigella, etc. showed significant higher abundance in CKD patients, whereas Flavobacterium, Blastomonas, Lautropia, etc. significantly declined in patients. Escherichia–Shigella achieved an acceptable diagnostic biomarker with area under the curve (AUC) value of 0.784 in the receiver operating characteristics (ROC) curve. In addition, CKD patients with pruritus (P-CKD) had a different bacterial community comparing to those without pruritus (non-P-CKD) and HC group. Several bacterial genera showing significant difference between P-CKD and non-P-CKD/HC, such as Oribacterium, significantly declined in P-CKD patients than that in the HC group, and Methylophaga significantly increased in P-CKD patients compared to that in HC subjects. Escherichia–Shigella was positively associated with the levels of pruritus severity, blood urea nitrogen (BUN), uric acid, and urine protein; Oribacterium was negatively associated with pruritus severity, whereas it was positively associated with estimated glomerular filtration rate (eGFR) and 24-h urine volume. The dysbiotic of skin microbiome in CKD patients and its association with pruritus and renal function shed a light on skin probiotics.